SOCIO-ECONOMIC DISTRESS IN PAKISTAN: A DIRECT CONSEQUENCE OF CONTRASTING PUBLIC POLICIES - Muhammad Ahmed Qadri; Suwaibah Qadri; Rabia Shakir (European Scientific Journal, ESJ, 2015)
Defining and interpreting socio economic status has become the most widely discussed issue among the researchers, due to its importance and contribution towards the policy making process. Public policies in Pakistan have never been so focused and intellectual as they are now these days. Presence of socio-economic distress has linkages with low socio-economic status at its back, which by extension, is due to weak public policies. Therefore, elimination of socio-economic distress seems rather trivial if the policy making is impeccable. Nevertheless, in the prevailing scenario of Pakistan, despite of having specialized policy makers implementing impeccable policies, the level of socio-economic distress has been found increasing. This paper attempts to examine the effects and relationship of historical public policies of Pakistan on prevailing socio-political economic distress. Since the current public policy is properly aligned with the prevailing issues, it is found that the increasing socio-economic distress in Pakistan is a direct consequence of contrasting public policies during the period of 80s and early 2000s.